Efektivitas Program Pelayanan Jaminan Kesehatan Daerah (JAMKESDA) Di Rumah Sakit Umum Kota Bitung - Pipa, Felix; Lengkong, Daicy; Rorong, Arie (Sam Ratulangi University, 2015)
ABSTRACT : Hospital is a health care institution that organizes personal health services in plenary thatprovides inpatient, outpatient, and emergency department. In connection with the Hospital opened healthservices through programs that one Regional Health Insurance program (JAMKESDA) which is aprogram for the poor that health care costs are guaranteed by the Government.This study is intended to answer the